MENINGKATAN MEMBACA KATA YANG BERAWALAN “M” DENGAN MENGGUNAKAN PERMAINAN PLASTISIN PADA ANAK TUNAGRAHITA SEDANG - Gusnita - Neni (Universitas Negeri Padang, 2012)
It’s using experiment approach in formed single subject research (SSR) with design A-B. This research to mean sure how many the correct answer student in reading prefix m in that prepared number form. The result of this research show that ability Tunagrahita RK in reading prefix m improve. The first condition baseline the doing for six days research. The first and the second meeting he can not read correctly and the third until six meeting he can read one prefix m .For changing levels are from seven and eight meeting he can read several prefix m, and the elevent and the twelve meeting he can read all of the prefix in word. Analyzed result show that : Variable amount that can be changed is one. That is ability student in reading prefix m ,percentage overlap is 0%,It is means there are improving to know prefix m for used it in class D III at SLB Lubuk Kilangan Padang, For that it is suggested for teacher using platisn playing for improving reading prefix m with using platisin playing for tunagrahita student.